Participation of Educational Institutions in Supporting Halal Tourism Destination Program through Development of Local Culture in East Lombok Regency - Fitriani, Fitriani; Suasti, Yurni (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this study is to obtain information about the participation of educational institutions in supporting Halal Tourism destination through development of local culture. This study uses qualitative descriptive approach by using observation, interview and questionnaire in data collection. Subjects to be studied in this study are head of education department, principal (SMAN 1 Rujukan Selong) and random people in the community. Sample is determined by purposive sampling technique to select school and proportional random sampling technique to select respondent. Study finding obtained from formal institutions: 1) good example from teacher as a model in character education, 2) curriculum that contain Halal Tourism, 3) contribution in improvement and maintenance of tourism facilities and infrastructures in location of tourism attractions, 4) held a parade on Islam holiday (PHBI) and Islamic art contest. Meanwhile, non-formal participations are: 1) construction of religious facilities, 2) selling halal food products in area of ​​tourist attraction, 3) selling Islamic souvenirs.